A large series of molecular and serological specimens to evaluate mother-to-child SARS-CoV-2 transmission: a prospective study from the Italian Obstetric Surveillance System. (January 2023) - Corsi Decenti, Edoardo; Salvatore, Michele Antonio; Mancon, Alessandro; Portella, Giuseppe; Rocca, Arianna; Vocale, Caterina; Donati, Serena; Alberi, Irene; Anelli, Gaia Maria; Baltaro, Federica; Bisulli, Maria; et al.
Highlights: SARS-CoV-2 vertical mother-to-child transmission was confirmed to be a rare event. The immunological response among infected mothers was good. An effective transfer of anti-SARS-CoV-2 antibodies to the newborn was detected. Vaccination during pregnancy should also be endorsed to protect infants aged <6 months old. Abstract: Objectives: To assay the presence of the SARS-CoV-2 genome in vaginal, rectal, and placental swabs among pregnant women and in newborn nasopharyngeal swabs and to investigate the immunological response and maternal antibody transfer through the umbilical cord blood and milk of unvaccinated mothers. Methods: Vaginal, rectal, and placental specimens, maternal and neonatal serum, and milk were collected from a wide cohort of pregnant Italian women with confirmed SARS-CoV-2 infection admitted to the hospital between February 25, 2020 and June 30, 2021. Samples were tested in selected reference laboratories according to a shared interlaboratory protocol. Results: Among 1086 enrolled women, the SARS-CoV-2 positive rate detected in all specimens ranged from 0.7% to 8.4%. Respectively, 45.2% of maternal sera collected during pregnancy and 39.7% of those collected at birth tested positive for immunoglobulin G, whereas 50.5% tested positive among neonates. Nasopharyngeal swabs were positive in 0.8% of the newborns, and immunoglobulin G was detected in 3.0% of the milk samples. The highest immunological response was recorded within 30 days during pregnancy and within 60 days of birth and in the neonatal population. Conclusion: Vertical transmission should be considered a rare event; although, a good maternal immunological response and antibodies transfer throughout the umbilical cord blood was detected.